Coagulopathy Due to Celiac Disease Presenting as Intramuscular Hemorrhage - Chen, Carolyn S. (Springer-Verlag, 2007)
INTRODUCTION: Celiac sprue most commonly presents with steatorrhea, abdominal pain, and weight loss. Celiac disease is now becoming more recognized for its atypical presentations. Anemia, osteoporosis, and childhood failure to thrive have been widely discussed. OBJECTIVE: In this paper, we present a case of nontraumatic intramuscular hemorrhage associated with prolongation of both prothrombin time and activated partial thromboplastin time. MAIN RESULTS: Coagulopathy, unmasked by the use of a nonsteroidal anti-inflammatory drug, was found to be attributable to vitamin K deficiency associated with malabsorption of multiple fat soluble vitamins. Celiac sprue was confirmed by small bowel biopsy. A review of the literature finds that, whereas asymptomatic prolongation of coagulation is relatively common in celiac sprue, clinical bleeding is a rare but described presentation. CONCLUSION: This case emphasizes the importance of recognizing hemorrhage as an atypical manifestation of celiac disease and offers the opportunity to review the clinical and laboratory evaluation of a patient who presents with unexplained hemorrhage.